Influence of Strategic Branding in Soft Drink Market in Indian and Malaysian Context: Study on Coca Cola to remain Top of the Mind Brand (TOMB) - Deshpande, Aditya; Kee, Daisy Mui Hung; Shankar, Divyaa; Segi, Soni; Charles, Esther Anthony; Parameswaran, Kumarendran; Vellmurugan, Malarveeli (AIBPM Publisher, 2020)
The aim of this research was to understand the influence of strategic branding in Soft Drink industry located in specific to India and Malaysia. This was demonstrated by example of various marketing strategies used by Coca-Cola, a very well-known brand all over the world. It operates in more than 200 countries and is listed as one of the most trusted brands for many years. With the presence in the both countries for more than 30 years, the company uses different Segmenting, Targeting, Positioning and Differentiation (STPD) strategy to cater varying needs to the consumers. Through analysis of consumer-buying in Indian and East Asian context is base pillar for success of Coca-Cola in the countries. The objectives of the project include analysing consumer needs of India and Malaysia regarding beverages-changing trends and the strategies and campaigns undertaken by Coca-Cola to cater vast diversified consumer base over the years. Both primary and secondary data collection were analysed with adequate sampling size of 180 respondents from both countries aided by questionnaire. Based on the analysis, the conclusions were drawn regarding company and recommendations are given for further improvement for company's performance.